2003
DOI: 10.1039/b300074p
|View full text |Cite
|
Sign up to set email alerts
|

Transfer hydrogenation using recyclable polyurea-encapsulated palladium: efficient and chemoselective reduction of aryl ketones

Abstract: A robust and recyclable palladium catalyst [Pd0EnCat] has been prepared by ligand exchange of polyurea-encapsulated palladium(II) acetate with formic acid, resulting in deposition of Pd(0) in the support material; Pd0EnCat is shown to be a highly efficient transfer hydrogenation catalyst for chemoselective reduction of a wide range of aryl ketones to benzyl alcohols.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

1
60
0

Year Published

2004
2004
2012
2012

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 106 publications
(62 citation statements)
references
References 5 publications
1
60
0
Order By: Relevance
“…[53] This catalyst mediates the room-temperature hydrogenolysis of 3-phenylepoxypropane in methanol, but a pressure of hydrogen is required and a mixture of the corresponding primary and secondary alcohols is obtained (Table 1, entry 9). [31,54] This substrate was also reduced by using a balloon fitted with hydrogen, EtOAc as the solvent, and a magnetically separable palladium catalyst, MPd, as described by Park et al in 2007 (Table 1, entry 10).…”
Section: Using Molecular Hydrogenmentioning
confidence: 99%
See 1 more Smart Citation
“…[53] This catalyst mediates the room-temperature hydrogenolysis of 3-phenylepoxypropane in methanol, but a pressure of hydrogen is required and a mixture of the corresponding primary and secondary alcohols is obtained (Table 1, entry 9). [31,54] This substrate was also reduced by using a balloon fitted with hydrogen, EtOAc as the solvent, and a magnetically separable palladium catalyst, MPd, as described by Park et al in 2007 (Table 1, entry 10).…”
Section: Using Molecular Hydrogenmentioning
confidence: 99%
“…Consequently, succinic acid is produced from the hydrogenolysis of both C-O bonds of the oxirane rather than from the hydrogenation of fumaric or maleic acid that would be issued from the dehydration of malic acid. Moreover, experiments with the use of deuterium led to the conclusion that the hydrogenolysis of the substrates into malic acids proceeds in a trans fashion [Equations (53) and (54)]. [114] Subsequently, trans-epoxysuccinic acid was hydrogenated at 100°C by using various supported palladium catalysts in either MeOH or under solvent-free conditions; the same three compounds were isolated, but it was proposed that fumaric or maleic acid is the source of succinic acid.…”
Section: Using Molecular Hydrogenmentioning
confidence: 99%
“…Polyurea as a support could eliminate the need for special ligands due to its strong chelation effect on metal species [10]. Microencapsulated Pd(OAc) 2 in polyurea by interfacial polymerization approach in O/W emulsion system has been demonstrated as a recoverable and reusable catalyst for hydrogenation of alkenes and ketones, hydrogenolysis of epoxides, and cross-coupling reactions [11][12][13][14][15]. To avoid the use of toxic solvent dichloromethane and expensive polymers, such as polymethylene diisocyanate and polyphenylene diisocyanate, a new immobilization system for encapsulating inorganic metal salts in polyurea via interfacial polymerization in W/O emulsion was developed for the first time, and the microencapsulated NiCl 2 has been demonstrated to be a recoverable and reusable catalyst for benzaldehyde reduction [16,17].…”
Section: Introductionmentioning
confidence: 99%
“…It has been demonstrated that metal species, such as Pd(OAc) 2 [4] can be encapsulated in polyurea and used as recoverable and reusable catalysts for alkenes hydrogenation [5], ketones hydrogenation [6], cross-coupling reaction [7], and hydrogenolysis of epoxides [8]. OsO 4 was also reported as a core material encapsulated in polyurea and has been effectively used as recoverable and reusable catalysts in dihydroxylation of olefins [9].…”
Section: Introductionmentioning
confidence: 99%